Comparative calorimetric study of non-amyloidogenic and amyloidogenic variants of the homotetrameric protein transthyretin - Shnyrov, Valery L. (2000)
Familial amyloidotic polyneuropathy (FAP) is an autosomal dominant hereditary type of amyloidosis involving amino acid substitutions in transthyretin (TTR). V30M-TTR is the most frequent variant, and L55P-TTR is the variant associated with the most aggressive form of FAP. The thermal stability of the wild-type, V30M-TTR, L55P-TTR and a non-amyloidogenic variant, T119M-TTR, was studied by high-sensitivity differential scanning calorimetry (DSC). The thermal unfolding of TTR is a spontaneous reversible process involving a highly co-operative transition between folded tetramers and unfolded monomers. All variants of transthyretin are very stable to the thermal unfolding that occurs at very high temperatures, most probably because of their oligomeric structure. The data presented in this work indicated that for the homotetrameric form of the wild-type TTR and its variants, the order of stability is as follows: wild-type TTRT119M-TTR>L55P-TTR>V30M-TTR, which does not correlate with their known amyloidogenic potential.